2013
DOI: 10.1002/pssa.201228705
|View full text |Cite
|
Sign up to set email alerts
|

Impact of varied sulfur incorporation on the device performance of sequentially processed Cu(In,Ga)(Se,S)2 thin film solar cells

Abstract: In order to improve the performance of chalcopyrite Cu(In 1 À x ,Ga x )(Se 1 À y S y ) 2 solar cells, the implementation of a bandgap widening at the absorber/buffer interface via an increase of the [S]/[S þ Se] ratio is investigated. In this work we examine industrially processed samples, which were fabricated via the deposition-reaction process with varied H 2 S pressure during rapid thermal processing (RTP). Precursors which were exposed to a crucial amount of sulfur during the RTP step resulted in samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 24 publications
3
29
0
4
Order By: Relevance
“…It has also been shown that an improvement from 14.5% to 16% efficiency can be obtained by annealing with elemental sulfur [6]. Among the explanations for the benefit of surface sulfurization are band gap widening of the surface [5] and passivation of deep defect states [6][7][8]. Annealing CIGSe in the presence of the metalorganic sulfur precursor ditertiarybutylsulfid has also been shown to result in formation of a S/Se surface gradient in coevaporated CIGSe [9].…”
Section: Introductionmentioning
confidence: 94%
“…It has also been shown that an improvement from 14.5% to 16% efficiency can be obtained by annealing with elemental sulfur [6]. Among the explanations for the benefit of surface sulfurization are band gap widening of the surface [5] and passivation of deep defect states [6][7][8]. Annealing CIGSe in the presence of the metalorganic sulfur precursor ditertiarybutylsulfid has also been shown to result in formation of a S/Se surface gradient in coevaporated CIGSe [9].…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, the front bandgap grading formed over a depth of about 0 to 200 nm which not only increases CBM but also lowers VBM, preventing surface state recombination by inhibiting photogenerated holes from migrating to electrolyte/CIGSSe interface 26 . In addition, surface sulfurization would passivate mid-gap recombination centers in the space charge region 36,41,42 . We have recently demonstrated that the surface state of CIGSSe can be passivated depending on sulfurization conditions, and thus increase photocurrent density 43 .…”
Section: Resultsmentioning
confidence: 99%
“…3(a). The J-V roll-over is an indication of the interface recombination [33,34]. This behavior was suppressed at temperature ranging from 300 K to 220 K after HLS post-treatment ( Fig.…”
Section: Impact Of the Hls Treatment On Cell Performancementioning
confidence: 87%